Network research experiences in New York and Eastern Europe: Lessons for the Southern US in understanding HIV transmission dynamics - Friedman, SR; Williams, L; Young, AM; Teubl, J; Paraskevis, D; Kostaki, E; Latkin, C; German, D; Mateu-Gelabert, P; Guarino, H; Vasylyeva, TI; Skaathun, B; et al. (Springer, 2018)
This paper presents an overview of different kinds of risk and social network methods and the kinds of research questions each can address.It also reviews what network research has discovered about how network characteristics are associated with HIV and other infections, risk behaviors, preventive behaviors, and care, and discusses some ways in which network-based public health interventions have been conducted. Based on this, risk and social network research and interventions seem both feasible and valuable for addressing the many public health and social problems raised by the widespread use of opioids in the US South.